A Correlative Study between the Radiologic and Pathologic Findings of Atherosclerosis of the Thoratic Aorta in the Aged - Yanase, Makoto; Okano, Kazutoshi; Muramatsu, Atsushi; Iwamoto, Masaaki; Okudaira, Masahiko (Nihon Rōnen Igakkai zasshi, 1968)
The clinical and radiologic findings of atherosclerosis of the aorta in a lateral chest film have been compared in 319 subjects above the age of 50 years. We have graded the atherosclerotic involvement with calcification of the aorta in the lateral chest film from class I to class IV. In class III or IV with evidence of marked atherosclerotic involvement of the aorta, postmorten examination confirmed the presence of atherosclerosis. This simple lateral chest X-ray examination constitutes a useful and easily applicable procedure in the detection of aortic atherosclerosis.